Ontology, Biosemiotics, and Set Theory: New Turns in Kristevan Studies - Nikolchina, Miglena (Acta Nova Humanistica: A Journal of Humanities Published by New Bulgarian University, 2024)
The papers collected in this volume were presented at the Eighth Meeting of the Kristeva circle, which took place in Julia Kristeva’s country of origin, Bulgaria, at the New Bulgarian University in Sofia, in May 2022. The small local organizing committee included Kristian Bankov, semiotician and Secretary General of the International Association for Semiotic Studies (IASS/AIS), Albena Stambolova, a writer and psychoanalyst, and myself, my research focus being on the juncture of literature and philosophy. I mention our research areas in order to foreground our ambition to have the conference address Kristeva’s various facets and, more specifically, to see the conference bridge the division and almost complete lack of interaction between studies exploring the early "linguistic" or semiotic Kristeva and those dealing with her work after her psychoanalytic turn in the 1980s. It could be argued that the semiotic (with or without the chora) is the only early concept that has made its way into studies post-dating the psychoanalytic turn: it is as if we are dealing with two Kristevas, distinct and even opposed to each other. Emphasizing the semiotic as process, as "semiotization," and juxtaposing it to "transubstantiation" in the title of the conference was intended to highlight and overcome this split: the first term evokes Kristeva’s early conception of the semiotizable chora; the second emerges from her study of Proust in the 1990s. Placing these concepts side by side was meant to foreground the shifts in Kristeva’s perspective as extending rather than replacing her early preoccupations.